Understanding wound healing and cancer in the skin - Tan, Mark Wei Yi (Nanyang Technological University, 2020)
The epidermis, being the outermost layer of the skin, is susceptible to wounds and cancer. In either of these events, the function of the skin as a barrier to external insults and regulation of several homeostatic processes is compromised. The dysregulation in chronic wounds and cancer need to be better understood in order for proper recovery of the epidermal barrier. With globalization and lifestyle changes, diabetic wounds are becoming increasingly common. Although the re-epithelialization process leading up to wound closure in normal wound healing is well studied, not much progress has been made in the understanding of diabetic wounds, leading to the insufficiency observed in existing therapeutic methods. Diabetic neuropathy has been reported to be strongly correlated with diabetic wounds. In my study, I demonstrated that keratinocytes are sensitive to acetylcholine stimulation, leading to the activation of the Src-ERK signaling axis and the upregulation of TGFβR2, thus promoting epithelial-mesenchymal transition. Under hyperglycemic conditions, this upregulation is suppressed by p38 MAPK activation, rendering the keratinocytes resistant to acetylcholine. Inhibition of p38 MAPK restored acetylcholine signaling, and therefore, epithelial-mesenchymal transition, of diabetic keratinocytes. Peroxisome proliferator-activated receptor β/δ is a lipid mediated nuclear receptor that exists as the predominant subtype in the epidermis and dermis. Although epidermal PPARβ/δ has been shown to be implicated in skin cancer, the role of PPARβ/δ in fibroblasts and its contribution to tumor progression remains obscure. Herein, I showed that deficiency of PPARβ/δ in fibroblasts led to changes in the LRG1-TGFβ1 signaling pathway that resulted in an increase in Nox4 in keratinocytes. The resulting increase in oxidative stress led to activation of the B-Raf-MEK pathway and subsequent upregulation of NRF2, as well as its downstream antioxidant enzymatic targets. The antioxidative response delayed tumor initiation and progression. Taken together, my studies conducted in this thesis provide valuable insight into the understanding of diabetic wounds and epithelial-mesenchymal crosstalk in skin cancer and highlight the importance of studying small non-proteinaceous biomolecules in these diseases.